Burmese asylum seekers in Thailand: still nowhere to turn - Isla Glaister; Chen Chen Lee (Forced Migration Review, 2008)
Until the Thai authorities and UNHCR can provide an asylumprocess that is systematic and fair, as opposed to one that isconditional on particular events and dates, the current asylumsystem will offer nothing more than pot luck.